Implementation of the Village Fund Direct Cash Assistance Policy (BLT-DD) for Pajar Bulan Village, Tanjung Sakti Pumi District, Lahat Regency, South Sumatra Province - Callia Puspa; Muhammad Anshori DM; Ike Apriani (Gayaku Publisher, 2022)
This study discusses the Policy Implementation of the 2021 Village Fund Direct Cash Assistance Program in Pajar Bulan Village, Tanjung Sakti District, PUMI, Lahat Regency, South Sumatra Province. This study aims to describe the implementation of the BLT and Village Fund program policies and analyze the factors that support and hinder the successful implementation of the BLT program in 2021 in Pajar Bulan Village, Tanjung Sakti District, PUMI, Lahat Regency, South Sumatra Province. Research using qualitative methods. The implementation of the program runs well, orderly, smoothly, and safely. Field implementation took the form of program socialization, data verification, distribution of cards, disbursement of funds, and preparation of reports. The implementation of the BLT-Village Fund policy in Pajar Bulan Village, Tanjung Sakti District, PUMI has covered the target group, in this case, poor families. Factors supporting the implementation of the BLT-Village Fund policy in Pajar Bulan Village, Tanjung Sakti Subdistrict, PUMI are the existence of complete and accurate data on prospective beneficiaries and the existence of uncomplicated and straightforward rules and procedures for distributing BLT-Village Funds. The inhibiting factors for implementing the policy were the dishonest character and characteristics of the village apparatus as implementers of the policy and the lack of available funds, so they had to propose again to the Regent. With the BLT-Village Fund policy in Pajar Bulan Village, Tanjung Sakti District, PUMI is expected to ease the burden on the lives of poor families as a result of the Covid-19 pandemic.